Factor VIII therapy for hemophilia A: current and future issues. Issue 3 (June 2014) - Aledort, Louis; Ljung, Rolf; Mann, Kenneth; Pipe, Steven
<x xml:space="preserve">Abstract</x> Hemophilia A is a congenital, recessive, X-linked bleeding disorder that is managed with infusions of plasma-derived or recombinant factor (F) VIII. The primary considerations in FVIII replacement therapy today are the: 1) immunogenicity of FVIII concentrates, 2) role of longer-acting FVIII products, 3) prophylactic use of FVIII in children and adults with severe hemophilia A, and 4) affordability and availability of FVIII products. Improving patient outcomes by increasing the use of FVIII prophylaxis, preventing or eliminating FVIII inhibitors, and expanding access to FVIII concentrates in developing countries are the major challenges confronting clinicians who care for patients with hemophilia A.